Motion Intention Analysis-Based Coordinated Control for Amputee-Prosthesis Interaction. (4th May 2010) - Wang, Fei; Wen, Shiguang; Wu, Chengdong; Zhang, Yuzhong; Li, Jincheng
Abstract : To study amputee-prosthesis (AP) interaction, a novel reconfigurable biped robot was designed and fabricated. In homogeneous configuration, two identical artificial legs (ALs) were used to simulate the symmetrical lower limbs of a healthy person. Linear inverted pendulum model combining with ZMP stability criterion was used to generate the gait trajectories of ALs. To acquire interjoint coordination for healthy gait, rate gyroscopes were mounted on CoGs of thigh and shank of both legs. By employing principal component analysis, the measured angular velocities were processed and the motion synergy was obtained in the final. Then, one of two ALs was replaced by a bionic leg (BL), and the biped robot was changed into heterogeneous configuration to simulate the AP coupling system. To realize symmetrical stable walking, master/slave coordinated control strategy is proposed. According to information acquired by gyroscopes, BL recognized the motion intention of AL and reconstructed its kinematic variables based on interjoint coordination. By employing iterative learning control, gait tracking of BL to AL was archived. Real environment robot walking experiments validated the correctness and effectiveness of the proposed scheme.